IMPLEMENTASI METODE EKSPERIMEN BERBANTUAN MEDIA KONKRET UNTUK MENINGKATKAN LONG TERM MEMORY DAN KEMAMPUAN DASAR KOGNITIF ANAK KELOMPOK B TAMAN KANAK-KANAK INDRA PRASTA KUTA - Leniasih, Wayan; Suyanta, I Wayan (PRATAMA WIDYA : JURNAL PENDIDIKAN ANAK USIA DINI, 2020)
This study aims to investigate the increase in long term memory and basic cognitive ability in group B children of Taman Kanak-kanak Indra Prasta Kuta and obstacles faced by children in learning using experimental method with concrete media. The implementation of this research was based on the results of preliminary observations indicating that the long term memory and basic cognitive ability of children are still low. This study was an action research conducted in two cycles. Subjects were children in group B (B5) of 17 children. The study was conducted in the second semester (even) in the Academic Year 2013-2014. The research procedure follows circles such as planning phase, implementation phase, observation phase, and reflection phase. The data were collected by using observation and taken by using descriptive qualitative method. The results show that the implementation of the experimental method with concrete media can improve (1) long term memory of children at the end of the first cycle by 41.18 % (7 children) achieving the expected standard with the categories of good and very good, and at the end of the second cycle, it increases by 100 % (17 children) achieving the expected standard with the categories of good and very good. (2) Cognitive basic ability of children at the end of the first cycle by 52.94% (9 children) achieving the expected standard with the categories of good and very good, and at the end of the second cycle, it increases by 100 % (17 children) achieving the expected standard with the categories of good and very good.Â Â